ESTRO IORT Task Force/ACROP recommendations for intraoperative radiation therapy in unresected pancreatic cancer - Calvo, Felipe A.; Krengli, Marco; Asencio, Jose M.; Serrano, Javier; Poortmans, Philip; Roeder, Falk; Krempien, Robert; Hensley, Frank W. (Radiotherapy and oncology, 2020)
Radiation therapy (RT) is a valuable component of multimodal treatment for localized pancreatic cancer. Intraoperative radiation therapy (IORT) is a very precise sub-component of RT that can intensify the irradiation effect for cancer involving an anatomically well-defined volume, generally delivered with electrons (IOERT). Unresectable disease categories benefit from dose-escalated chemoradiation strategies in the context of active systemic therapy and potential radical surgery. Prolonged preoperative treatment may act as a filter for selecting patients with occult resistant metastatic disease. Long-term survivors were observed among unresected patients treated with external beam RT and an IOERT boost (OS 6% at 3 years; 3% >5 years). Improvement of local control through higher RT doses has an impact on the survival of patients with a lower tendency towards disease spread. IOERT is a well-accepted asset in the clinical scenario (maturity and reproducibility of results, albeit of low official level of evidence) and extremely accurate in terms of dose-deposit characteristics and normal tissue sparing. It is a technique that can be integrated with systemic therapy and surgical progress. International guidelines (National Comprehensive Cancer Network or NCCN guidelines) currently recommend the use of IOERT in cases of close surgical margins and residual disease. We report the ESTRO/ACROP recommendations for performing IOERT in unresected pancreatic cancer.